Designing and Building a Web-Based Book Sales and Tenancy Platform - Candra Iswayudi; Irwan Alnarus Kautsar; Suprianto Suprianto (Procedia of Engineering and Life Science, 2022)
Infrastructure development that continues to increase is one of the conveniences for the community to use the internet, which can access various digital content such as websites, chat, shopping, and others. More than half of the population in Indonesia accesses the internet every day, if it is used to make a product branding, it will be more time efficient and save costs. Books are one of the products that must exist in every generation because they are an important source of information in everyday events. This study aims to create a place for people who want to sell books that can make it easier for buyers or consumers. Utilizing a website that can speed up an activity and save time to sell or find books for sellers and consumers. This research was built using Python as a programming language, Flask Framework as a system framework, sqlite3 as data storage, and bootstrap 5 as a display foundation combined with style changes through CSS (Cascading Style Sheets). Agile development is a method used to develop marketplace platforms. The result of this research is a web-based book rental and tenancy marketplace platform.